2019
DOI: 10.1186/s12989-019-0327-z
|View full text |Cite
|
Sign up to set email alerts
|

Silicon dioxide nanoparticles induce insulin resistance through endoplasmic reticulum stress and generation of reactive oxygen species

Abstract: Background Silicon dioxide nanoparticles (SiO2 NPs) are one of the most widely utilized NPs in various food sectors. However, the potential endocrine toxicity of SiO2 NPs has not been characterized. Results In the present study, mice were orally administered a series of doses of SiO2 NPs. All doses of SiO2 NPs were absorbed into the blood, liver, and pancreas of the mice. Administration of 100 mg/kg bw (body weight) of SiO2 NPs signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 31 publications
1
41
0
1
Order By: Relevance
“…This is reminiscent of the expression pattern of Nrf2, a crucial stress regulator to reduce the ROS, which is a key factor in sensitizing insulin signaling 5557 . It has also been confirmed that up-regulation of the Nrf2 expression both by genetic manipulation and pharmacological interference, can significantly decrease the content of ROS and ameliorate IR and T2D 58,59 . In the mice supplement with metformin, the significant up-regulation in the expression of Nrf2 and its downstream target genes ( Gclc , Cat and Ho-1 ) occurred, which further alleviated IR and over-oxidation.…”
Section: Discussionmentioning
confidence: 86%
“…This is reminiscent of the expression pattern of Nrf2, a crucial stress regulator to reduce the ROS, which is a key factor in sensitizing insulin signaling 5557 . It has also been confirmed that up-regulation of the Nrf2 expression both by genetic manipulation and pharmacological interference, can significantly decrease the content of ROS and ameliorate IR and T2D 58,59 . In the mice supplement with metformin, the significant up-regulation in the expression of Nrf2 and its downstream target genes ( Gclc , Cat and Ho-1 ) occurred, which further alleviated IR and over-oxidation.…”
Section: Discussionmentioning
confidence: 86%
“…It is not clear whether the SAS used by Liang et al (2018) and Yun et al (2015) is compliant with the E 551 specifications. Three recent studies using relatively low dose levels (from 2 up to 200 mg/kg bw/d), however, did report effects, including effects on the liver (Boudard et al 2019;Hu et al 2019;Tassinari et al 2020). The study by Boudard et al (2019) demonstrated that chronic exposure (18 months) of mice to 4.8 mg/kg bw/d precipitated SAS (NM-200) via the drinking water triggered renal and liver inflammation accompanied by amyloidosis in kidney glomeruli and in perivascular regions.…”
Section: New Oral Toxicity Studiesmentioning
confidence: 97%
“…on liver and kidney (Boudard et al 2019;Boudard et al 2020). A subchronic study using relatively low dose levels was performed by Hu et al (2019), in which mice were treated for 18 weeks with different doses pyrogenic or colloidal silica particles (both NPs and MPs) focusing on endocrine effects and blood glucose levels. Exposure to 100 mg/kg bw/d (the only tested dose) of pyrogenic NPs resulted in lowered superoxide dismutase (SOD) and glutathione (GSH) levels and increased malonyl dialdehyde (MDA) levels after 7 weeks in serum and in the liver, indicating reactive oxygen species (ROS) generation in the liver.…”
Section: New Oral Toxicity Studiesmentioning
confidence: 99%
“…Recently, it has been reported in human hepatoma cells that SiO 2 -NPs promote oxidative stress through the ER stress [218], and leads to the induction of TNF-α and activates MAPK pathways [219]. SiO 2 -NPs induced ER stress also leads to the activation of NF-κB, leading to the expression of interferons [220]. It has been further reported that SiO 2 -NPs persuade the expression of MAP kinase regulated transcription factors like CYMC and CJUN [219].…”
Section: Quartz and Silica Nanoparticlesmentioning
confidence: 98%